Saddle embolism treated by thrombolysis and thrombus aspiration via bilateral femoral artery puncture catheter: A case report. Issue 13 (March 2018) - Min, Jie; Zhang, Guangqiang
Abstract: Introduction: Abdominal aortic saddle embolism is a rare and severe disease with the manifestation of abrupt onset, rapid progression and high mortality. Endovascular therapy becomes a new option for this disease due to its minor trauma, less complications, no requirement for general anesthesia or abdominal incisions, and shorter hospitalization duration. Methods: A 50-year-old female was diagnosed as abdominal aortic saddle embolism, and thrombus aspiration was given immediately via bilateral femoral artery puncture catheter along with artery indwelling catheter thrombolysis. Results: The saddle embolism was removed completely. After 1-month follow-up, the computed tomography angiography (CTA) examination showed neither stenosis nor thrombus in the abdominal aorta and iliac artery. The patient achieved perfect outcome. Conclusions: Endovascular therapy may be an optional solution for saddle embolism.